Β‒hairpin polypeptides by design and selection. Issue 2 (2003) - Skelton Skelton, Nicholas J. Nicholas J.; Blandl Blandl, Tamas Tamas; Russell Russell, Stephen J. Stephen J.; Starovasnik Starovasnik, Melissa A. Melissa A.; Cochran Cochran, Andrea G. Andrea G.
Abstract : We have developed polypeptide scaffolds that readily adopt a β ‒hairpin conformation (a pair of antiparallel strands connected by a turn) in solution. The study of such peptides allows us to understand the factors that govern stability and folding of these motifs in proteins, and permits mimicry of functionally important regions of proteins. Spectroscopic and biophysical methods have been used to characterize the conformational preferences and stability of these peptides, with a strong emphasis on using restraints generated from 1 H NMR spectroscopy to determine their three‒dimensional structure. By optimization of inter‒strand interactions, we have developed highly stable disulfide‒cyclized and linear β ‒hairpin peptides. In particular, tryptophan residues at non‒hydrogen bonded strand sites (NHB) are highly stabilizing. A variety of turn types have been presented from these scaffolds, suggesting that they might generally be useful in turn presentation. Interestingly, β ‒hairpin peptides (containing a disulfide and a NHB tryptophan) have recently been discovered as antagonists of protein–protein interactions from naïve peptide libraries displayed on phage. Comparison of one such β ‒hairpin peptide with an α ‒helical peptide of very similar sequence provides further insight into the role that residue type and context play in determining polypeptide conformation.